Sekolah Sebagai Institusi Sosial Untuk Membangun Moralitas Di MTs Ma’arif NU 1 Jatilawang : Analisis Durkheimian - Tia Mugi Winasih; Muh. Hanif (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2025)
The focus of this research is to find out how Durkheimian theory is applied to the role of schools as social institutions in building shared morality at MTs Ma'arif Nu 1 Jatilawang. Another focus is to find out how schools become a link for the formation of values, norms, rules and patterns of interaction solidarity and morality which become habituation for students, teachers and parents. Apart from that, to find out how Durkheiman's theory will answer the extent to which MTs Manusaja contributes to realizing the pillars of morality in the personalities of teachers, parents and students in their environment. So that good habits, mutual trust, reciprocal relationships and positive social behavior emerge. In this research, the interview method was used to obtain data in accordance with the research focus. This research is descriptive qualitative research. The appropriate method for collecting data is direct observation of students and teachers as well as interviews with the head of the madrasah, student teachers and parents. The results of this research will certainly add to the general benefits of educational institutions, especially Islamic-based educational institutions or general formal institutions.